PRICING A CLASS OF EXOTIC OPTIONS VIA MOMENTS AND SDP RELAXATIONS - Lasserre, J. B.; Prieto-Rumeau, T.; Zervos, M. (Mathematical finance, 2006)
We present a new methodology for the numerical pricing of a class of exotic derivatives such as Asian or barrier options when the underlying asset price dynamics are modeled by a geometric Brownian motion or a number of mean‐reverting processes of interest. This methodology identifies derivative prices with infinite‐dimensional linear programming problems involving the moments of appropriate measures, and then develops suitable finite‐dimensional relaxations that take the form of semidefinite programs (SDP) indexed by the number of moments involved. By maximizing or minimizing appropriate criteria, monotone sequences of both upper and lower bounds are obtained. Numerical investigation shows that very good results are obtained with only a small number of moments. Theoretical convergence results are also established.